Website-Based Coin-Operated Charging Station Management System - Adam Samudera (Indonesian Journal of Electronics and Computer Technology, 2026)
The increasing use of mobile devices has led to a growing demand for charging facilities in public spaces, including coffee shops. This trend often results in uncontrolled electricity consumption, causing additional operational costs for business owners. This study aims to design and develop a website-based coin-operated charging station management system to enable real-time monitoring of electricity usage. The research adopted the Waterfall model within the System Development Life Cycle (SDLC), encompassing the phases of planning, analysis, design, testing, and implementation. The proposed system was developed using the CodeIgniter 3 framework, PHP, HTML, CSS, MySQL, and a web-based monitoring platform integrated with a coin sensor and an energy monitoring module. The results demonstrate that the system is capable of monitoring and displaying real-time electrical parameters, including current, power, voltage, and coin transaction data, while simultaneously storing the collected information in a database for historical monitoring and analysis. The developed system provides coffee shop operators with an efficient and reliable solution for monitoring electricity consumption, thereby supporting better energy management and reducing unnecessary operational costs.